Thin film, composite thin film, photoelectric device and display device
By using doped selenide two-dimensional nanomaterials to prepare thin films, the problem of hole injection difficulties in conventional QLED devices is solved, and the luminous efficiency and service life of optoelectronic devices are improved.
Patent Information
- Application Number
- CN202311282312.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-28
AI Technical Summary
In conventional QLED devices, the size of the organic material fragments of the quantum dot functional layer and the quantum dots have a large difference, making it difficult for holes to inject into the quantum dot luminescence layer, resulting in carrier imbalance and reducing luminescence efficiency.
Thin films are prepared using doped selenide two-dimensional nanomaterials to improve hole transport capability through the conductivity and thermal conductivity of the two-dimensional nanomaterials, and the conductivity and hot carrier transport capability are improved through the setting of doped elements.
The hole injection quantity and luminous efficiency of optoelectronic devices are improved, the service life of optoelectronic devices is extended, and the generation of leakage current is prevented.
Smart Images

Figure CN119730573A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of display technology, and more specifically, to a thin film, a composite thin film, a photoelectric device and a display apparatus. Background Art
[0002] In recent years, with the rapid development of display technology, quantum dot light-emitting diodes (QLEDs) using semiconductor quantum dot materials as the light-emitting layer have received widespread attention. Their excellent characteristics such as high color purity, high luminous efficiency, adjustable luminous color and stable device make quantum dot light-emitting diodes have broad application prospects in the fields of flat panel display and solid-state lighting.
[0003] In conventional QLED devices, the size of the organic material fragments in the quantum dot functional layer is quite different from that of the quantum dots, so it is difficult to inject holes into the quantum dot light-emitting layer, resulting in an imbalance in the number of carriers in the quantum dot light-emitting layer and low luminescence efficiency of the optoelectronic device. Summary of the invention
[0004] The embodiments of the present application aim to provide a thin film, a composite thin film, an optoelectronic device and a display device.
[0005] The present application provides a thin film, which adopts the following technical solution:
[0006] A film comprising:
[0007] A first film, wherein the first film comprises a selenide two-dimensional nanomaterial containing a doping element, wherein the atomic radius of the doping element is smaller than the atomic radius of the selenium element.
[0008] Furthermore, the atomic ratio of the doping element to the selenium element is (0.5-1):1.
[0009] Further, the material of the selenide two-dimensional nanomaterial is selected from transition metal selenides, and the transition metal selenides are selected from at least one of molybdenum selenide, titanium selenide, vanadium selenide, rhenium selenide, cadmium selenide, zirconium selenide, hafnium selenide, tantalum selenide, tungsten selenide, and manganese selenide; and / or
[0010] The doping element is selected from Group VIA elements; and / or
[0011] The thickness of the first film is in the range of 20 to 50 nm.
[0012] The present application also provides a composite film, which adopts the following technical solution:
[0013] A composite film, comprising:
[0014] A first film, wherein the first film is the film as described above;
[0015] The second film, the first film is arranged on the second film, and the second film is prepared by a composite material, wherein the composite material includes a mixed transition metal oxide, a molten salt and aluminum.
[0016] Furthermore, in the composite material, the mass percentage of the transition metal oxide is 40wt% to 60wt%;
[0017] The mass percentage of the molten salt is 30wt% to 60wt%;
[0018] The mass percentage of aluminum is 10wt% to 30wt%.
[0019] Furthermore, the composite film also includes a third film, the first film is arranged between the second film and the third film, and the third film is made of an interface modification material.
[0020] Furthermore, the interface modification material is a hollow-shell structure, wherein in the hollow-shell structure, the material of the shell is selected from transition metal compounds.
[0021] Further, the transition metal oxide is selected from at least one of molybdenum trioxide, titanium dioxide, vanadium trioxide, rhenium heptoxide, chromium trioxide, zirconium dioxide, hafnium oxide, tantalum pentoxide, tungsten trioxide and manganese dioxide; and / or
[0022] The molten salt is selected from AlCl3 or Al2O3; and / or
[0023] The transition metal compound is selected from at least one of molybdates, titanates, vanadates, rhenates, cadmates, zirconates, hafnates, tantalates, tungstates and manganates; and / or
[0024] The thickness of the second film is in the range of 20 to 50 nm; and / or
[0025] The diameter of the hollow-shell structure is in the range of 5 to 10 nm; and / or
[0026] The thickness of the third film is in the range of 5 to 10 nm.
[0027] Furthermore, the first film, the second film and the third film have the same transition metal element.
[0028] The present application also provides a photoelectric device, which adopts the following technical solution:
[0029] A photoelectric device, comprising:
[0030] A stacked anode layer, a hole functional layer, a quantum dot light emitting layer, an electronic functional layer and a cathode layer;
[0031] Wherein, the hole functional layer adopts the composite film as described above.
[0032] Furthermore, the composite film includes a first film, a second film and a third film which are stacked;
[0033] The second film is disposed on the anode layer and serves as a hole injection layer;
[0034] The first film is disposed on the second film to serve as a hole transport layer;
[0035] The third film is arranged on the first film and serves as an interface modification layer.
[0036] Further, the material of the anode layer and / or cathode layer includes at least one of a metal, a carbon material and a metal oxide, the metal includes at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes at least one of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a doped or undoped metal oxide, including at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the composite electrode includes at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or
[0037] The electronic functional layer includes an electron transport layer, and the material of the electron transport layer includes an inorganic material and / or an organic material. The inorganic material is selected from at least one of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element includes at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds; and / or
[0038] The material of the quantum dot light-emitting layer includes at least one of a single structure quantum dot and a core-shell structure quantum dot. The core material and the shell material of the core-shell structure quantum dot are selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds, wherein the II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, At least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and Group IV-VI compounds include SnS, SnSe, SnTe, PbS, PbSe, PbTe, At least one of SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the III-V compounds include GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs , AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compounds include but are not limited to at least one of CuInS2, CuInSe2 and AgInS2.
[0039] The present application also provides a display device, which adopts the following technical solution:
[0040] A display device comprises the optoelectronic device as described above.
[0041] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0042] The present application provides a film prepared from a doped selenide two-dimensional nanomaterial, which has good electrical and thermal conductivity of the two-dimensional nanomaterial itself, so that the film has good hot carrier transport capability, and utilizes the characteristic that defect states are easily generated at the edges of the two-dimensional nanomaterial assembly during the stacking process to capture excess electrons and prevent the generation of leakage current; in addition, by doping the two-dimensional nanomaterial and setting the atomic radius of the doping element to be smaller than the atomic radius of the selenium element, the electrical conductivity and hot carrier transport capability of the composite film are further improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the scheme of the present application, a brief introduction is given below to the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0044] Figure 1 is a schematic diagram of the structure of the composite film of an embodiment of the present application;
[0045] Figure 2 is a schematic structural diagram of an optoelectronic device according to an embodiment of the present application;
[0046] Figure 3 It is a current density-voltage curve diagram of a single hole device comprising composite thin film embodiments 1 to 7 and composite thin film comparative example 1 of the present application.
[0047] Reference numerals:
[0048] 1. Anode layer; 2. Hole functional layer; 21. Second thin film; 22. First thin film; 23. Third thin film; 3. Quantum dot light-emitting layer; 4. Electron transport layer; 5. Cathode layer. DETAILED DESCRIPTION
[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in the specification of the application herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned drawings are intended to cover non-exclusive inclusions. The terms "first", "second", etc. in the specification and claims of this application or the above-mentioned drawings are used to distinguish different objects, not to describe a specific order.
[0050] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0051] The structure of a conventional optoelectronic device is usually composed of an anode layer / hole functional layer / quantum dot light-emitting layer / electronic functional layer / cathode layer. The anode layer is usually made of ITO material, and the hole functional layer includes a hole transport layer. Among them, the traditional hole transport layer is usually made of organic materials such as TFB or PVK.
[0052] When organic materials such as TFB or PVK are used as hole transport materials, holes are difficult to inject into the light-emitting layer due to the large size difference between the organic material fragments and the quantum dot materials. This results in weak hole transport capacity in conventional optoelectronic devices, and the number of holes injected into the quantum dot light-emitting layer is less than the number of electrons injected, resulting in charge imbalance in the quantum dots, which in turn affects the luminescence efficiency of the optoelectronic device.
[0053] The hole functional layer also includes a hole injection layer, which is arranged between the anode layer and the hole transport layer. Among them, the traditional hole injection layer is usually prepared using polyethylene dioxythiophene / polystyrene sulfonate (PEDOT:PSS) material, and the HOMO energy level of the PEDOT:PSS material is well matched with the ITO work function to achieve effective hole injection and transport.
[0054] Since the PEDOT:PSS material of the hole injection layer is acidic, during the preparation of the optoelectronic device, the diffusion of acidic substances can easily affect the stability of the optoelectronic device, easily lead to electron leakage and thus form leakage current, affecting the luminous efficiency and service life of the optoelectronic device.
[0055] Currently, the hole transport capacity in optoelectronic devices can be improved by transferring hot carriers under low pressure conditions. Therefore, improving the thermal conductivity and electrical conductivity of the hole functional layer is a key link in improving the luminous efficiency of optoelectronic devices.
[0056] Based on the above problems, an embodiment of the present application provides a composite film, including a first film 22 .
[0057] The first film 22 includes a selenide two-dimensional nanomaterial containing a doping element, wherein the atomic radius of the doping element is smaller than the atomic radius of selenium.
[0058] The present application provides a composite film prepared from a doped selenide two-dimensional nanomaterial, which has good electrical and thermal conductivity of the two-dimensional nanomaterial itself, so that the composite film has good hot carrier transport capability, and uses the characteristic that the edges of the two-dimensional nanomaterial assembly are prone to produce defect states during the stacking process, so as to capture excess electrons and prevent the generation of leakage current; in addition, by doping the two-dimensional nanomaterial, and setting the atomic radius of the doping element to be smaller than the atomic radius of the selenium element, the conductivity and hot carrier transport capability of the composite film are further improved. In some embodiments, the atomic ratio of the doping element to the selenium element is (0.5:1) to (1:1), for example, the atomic ratio of the doping element to the selenium element is 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1.
[0059] The embodiment of the present application further improves the electrical conductivity of the selenide two-dimensional nanomaterial by doping the doping element into the selenide two-dimensional nanomaterial while ensuring the thermal conductivity of the composite material itself, thereby improving the carrier mobility, so that the first film prepared using the doped selenide two-dimensional nanomaterial has improved hole transport capacity and increased the number of hole injections.
[0060] In some embodiments, the doping element is a VIA group element of the same family as the selenium element, and the atomic radius of the doping element is smaller than that of the selenium element. In this embodiment, the doping element is sulfur, the atomic radius of the sulfur atom is 0.104nm, and the atomic radius of the selenium atom is 0.122nm.
[0061] In some embodiments, the material of the selenide two-dimensional nanomaterial is selected from transition metal selenides, wherein the transition metal selenide is selected from one of molybdenum selenide (MoSe2), titanium selenide (TiSe2), vanadium selenide (VSe2), rhenium selenide (ReSe2), cadmium selenide (CrSe), zirconium selenide (ZrSe2), hafnium selenide (HfSe2), tantalum selenide (TaSe2), tungsten selenide (WSe2), and manganese selenide (MnSe). In this embodiment, the selenide two-dimensional nanomaterial is preferably molybdenum selenide (MoSe2).
[0062] In some embodiments, the thickness of the first film 22 is in the range of 20 to 50 nm.
[0063] Specifically, the thickness of the first thin film 22 is in the range of about 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm.
[0064] See also Figure 1 As shown, based on the above-mentioned film, an embodiment of the present application further provides a composite film, including: a first film 22 and a second film 21 .
[0065] The first film 22 is the film as described above.
[0066] The second film 21 , the first film 22 is arranged on the second film 21 , and the second film 21 is made of a composite material.
[0067] In some embodiments, the composite material includes a mixed transition metal oxide, a molten salt, and aluminum; in this embodiment, the transition metal oxide in the second film 21 and the transition metal selenide in the first film 22 include the same transition metal.
[0068] In the embodiment of the present application, the second film 21 and the first film 22 contain the same transition metal, so that when the composite film is prepared by a solution method, the second film 21 and the first film 22 will not be penetrated by the solvent, thereby improving the internal chemical stability of the composite film and improving the service life of the composite film; in addition, the first film 21 provided by the hole injection layer is prepared by mixing transition metal oxides, aluminum and molten salts, so that a reaction occurs in the hole injection layer 21 to release heat, heat the carriers to form hot carriers and transfer the heat to the hole transport layer 22 and heat the hole transport layer 22; in addition, by adding molten salt to the composite material, the temperature of the reaction release is reduced, so as to improve the hole transport efficiency of the composite film and increase the number of holes injected into the composite film; in addition, the transition metal element and aluminum oxide generated by the reaction of transition metal oxides, aluminum and molten salts can improve the surface properties of the hole injection layer 21, improve the roughness of the hole injection layer 21, thereby improving the film uniformity of the composite film.
[0069] In some embodiments, the transition metal oxide is selected from one of molybdenum trioxide (MoO3), titanium dioxide (TiO2), vanadium trioxide (V2O3), rhenium heptoxide (Re2O7), chromium trioxide (Cr2O3), zirconium dioxide (ZrO2), hafnium oxide (HfO2), tantalum pentoxide (Ta2O5), tungsten trioxide (WO3), and manganese dioxide (MnO2). In this embodiment, the transition metal oxide in the hole injection material is preferably molybdenum trioxide (MoO3).
[0070] In some embodiments, the mass percentage of the transition metal oxide in the hole injection material is 40wt% to 60wt%; the mass percentage of the molten salt is 30wt% to 60wt%; and the mass percentage of the aluminum is 10wt% to 30wt%.
[0071] Specifically, the hole injection material can be set to: the mass percentage of the transition metal oxide is 60wt%, the mass percentage of the molten salt is 30wt%, and the mass percentage of the aluminum is 10wt%; or, the mass percentage of the transition metal oxide is 40wt%, the mass percentage of the molten salt is 30wt%, and the mass percentage of the aluminum is 30wt%.
[0072] In some embodiments, the transition metal compound is selected from one of molybdate, titanate, vanadate, rhenate, cadmate, zirconate, hafnium salt, tantalate, tungstate, and manganate. In this embodiment, the transition metal compound in the interface modification material is preferably molybdate, and the molybdate can be one of nickel molybdate (NiMoO4), cobalt molybdate (CoMoO4), and zinc molybdate (MoO4Zn).
[0073] In some embodiments, the thickness of the second film 21 ranges from 20 to 50 nm;
[0074] Specifically, the thickness of the second thin film 21 is in the range of about 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm.
[0075] Please continue reading Figure 1 As shown, in some embodiments, the composite film further includes a third film 23, the first film 21 is disposed between the second film 22 and the third film 23, and the third film 23 is made of an interface modification material.
[0076] In the embodiment of the present application, the third film 23 is disposed on the first film 22 to reduce the difference between the size of the hole transport material and the quantum dots, thereby improving the hole injection capability.
[0077] In some embodiments, the interface modification material is a hollow-shell structure, wherein the shell material of the hollow-shell structure is selected from transition metal compounds; in this embodiment, the interface modification material has the same transition metal element as the transition metal oxide and selenide.
[0078] The first film 22 and the third film 23 in the embodiment of the present application both contain the same transition metal, so that when the composite film is prepared by a solution method, the third film 23 and the first film 22 will not be penetrated by the solvent, thereby improving the internal chemical stability of the composite film and increasing the service life of the composite film. In addition, the interface modification material adopts a hollow-shell structure, so that when the third film 23 receives the carriers transferred by the first film 22, the carriers enter the interior of the hollow-shell structure and then form excitons, thereby delaying the recombination time of holes and electrons, thereby increasing the service life of the optoelectronic device containing the above-mentioned composite film.
[0079] In some embodiments, the diameter of the hollow-shell structure is in the range of 5 to 10 nm; the thickness of the third film 23 is in the range of 5 to 10 nm.
[0080] Specifically, the diameter range of the hollow-shell structure is 5nm, 6nm, 7nm, 8nm, 9nm, and 10nm.
[0081] Specifically, the thickness of the third film 23 ranges from 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, and 10 nm.
[0082] Preferably, the thickness of the third film 23 is the same as the diameter of the hollow-shell structure. Through this arrangement, a single layer of interface modification material is formed in the third film 23, so that the third film 23 has the function of delaying the formation of excitons by holes and electrons without affecting the number of hole injections, thereby achieving the goal of extending the service life of the optoelectronic device containing the above-mentioned composite film while improving the luminous efficiency of the optoelectronic device.
[0083] See also Figure 3 As shown, an embodiment of the present application further provides a photoelectric device, comprising: a stacked anode layer 1, a hole functional layer 2, a quantum dot light-emitting layer 3, an electron functional layer 4 and a cathode layer 5, wherein the hole functional layer 2 adopts the above-mentioned composite film.
[0084] In this embodiment, the optoelectronic device includes:
[0085] The anode layer 1 and the cathode layer 5 are arranged opposite to each other.
[0086] The hole functional layer 2 is arranged between the anode layer 1 and the cathode layer 5, and is arranged close to the anode layer 1. The hole functional layer 2 adopts the above-mentioned composite film, wherein the composite film includes a first film 22, a second film 21 and a third film 23 which are stacked; the second film 21 is arranged on the anode layer as a hole injection layer; the first film 22 is arranged on the first film 21 as a hole transport layer; the third film 23 is arranged on the first film as an interface modification layer.
[0087] The electronic functional layer 4 is disposed between the anode layer 1 and the cathode layer 5 and is disposed close to the cathode layer 5 .
[0088] The quantum dot light-emitting layer 3 is disposed between the hole functional layer 2 and the electron functional layer 4 .
[0089] In some embodiments, the material of the anode layer 1 and / or the cathode layer 5 includes at least one of a metal, a carbon material and a metal oxide, the metal includes at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes at least one of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a doped or undoped metal oxide, including at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, and the composite electrode includes at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2.
[0090] The electronic functional layer 4 includes an electron transport layer, and the material of the electron transport layer includes inorganic materials and / or organic materials. The inorganic material is selected from at least one of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element includes at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds.
[0091] The material of the quantum dot light-emitting layer 3 includes at least one of a single structure quantum dot and a core-shell structure quantum dot. The core material and the shell material of the core-shell structure quantum dot are selected from at least one of a II-VI group compound, a IV-VI group compound, a III-V group compound and a I-III-VI group compound. The II-VI group compound includes CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe , at least one of CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and Group IV-VI compounds include SnS, SnSe, SnTe, PbS, PbSe, PbTe, At least one of SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe and SnPbSTe, and the III-V compounds include GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs , AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, and the I-III-VI group compounds include but are not limited to at least one of CuInS2, CuInSe2 and AgInS2.
[0092] The optoelectronic device provided in the embodiment of the present application adopts the above-mentioned composite film as the hole functional layer 2. At the hole injection layer, the heat generated by the reaction of transition metal oxide, aluminum and molten salt can heat the holes entering the hole functional layer 2 to form hot carriers and then transmit them to the quantum dot light-emitting layer 3. Under low-pressure conditions, the hole mobility can be improved, the hole transmission capacity can be improved, thereby increasing the number of hole injections, promoting the hole-electron number balance in the quantum dot light-emitting layer 3, and improving the luminous efficiency of the optoelectronic device; in addition, by arranging a third film 23 as an interface modification layer on the hole functional layer 2, the non-radiative recombination of holes and electrons in the non-luminescent layer is reduced, the recombination time of holes and electrons is delayed, and the service life of the optoelectronic device is improved; by utilizing the selenide two-dimensional nanomaterials stacked in the first film 22, the hole transport layer of the hole functional layer 2 has good thermal conductivity and electrical conductivity, and the electrical conductivity of the hole transport film is further improved by doping with sulfur; wherein, in the process of stacking the selenide two-dimensional nanomaterials, defect states are easily generated, thereby being able to capture excess electrons, preventing the generation of leakage current, and further improving the luminous efficiency and service life of the optoelectronic device.
[0093] In this embodiment, the light-emitting device is a positive light-emitting device, and the structure of the light-emitting device is anode layer 1 / hole functional layer 2 / quantum dot light-emitting layer 3 / electron functional layer 4 / cathode layer 5. In other embodiments, the light-emitting device can also be an inverted light-emitting device, and the structure of the light-emitting device is cathode layer 5 / electron functional layer 4 / quantum dot light-emitting layer 3 / hole functional layer 2 / anode layer 1.
[0094] An embodiment of the present application further provides a display device, which includes the above-mentioned light-emitting device.
[0095] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.
[0096] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.
[0097] Composite film embodiment 1
[0098] Step (1), providing a substrate.
[0099] Step (2), preparing a first ink, and forming a hole injection layer on the substrate through the first ink, wherein the thickness of the hole injection layer is 40 nm.
[0100] Wherein, the first ink is a PEDOT:PSS solution.
[0101] Step (3), preparing a second ink, and forming a hole transport layer on the hole injection layer by the second ink, wherein the thickness of the hole transport layer is 20 nm.
[0102] Wherein, the second ink is configured by the following steps:
[0103] 15 ml of n-octylamine and 13 ml of ethanol were mixed to form a mixed solvent, 0.32 mmol of sulfur powder and 0.79 mmol of selenium powder were dissolved in the mixed solvent, 0.064 mmol of ammonium molybdate was added after full dissolution, and the mixture was transferred to a sealed oven and reacted at 180°C for 12 hours. The reaction product was washed with ethanol to obtain S-doped MoSe2 two-dimensional nanomaterial (the atomic ratio of S:Se is 1:1), and the S-doped MoSe2 two-dimensional nanomaterial was dissolved in an ethanol solution to form a second ink.
[0104] Composite film embodiment 2
[0105] The difference between this embodiment and the composite film embodiment 1 is that, in step (3), the second ink is configured by the following steps:
[0106] 15 ml of n-octylamine and 13 ml of ethanol were mixed to form a mixed solvent, 0.16 mmol of sulfur powder and 0.79 mmol of selenium powder were dissolved in the mixed solvent, 0.064 mmol of ammonium molybdate was added after full dissolution, and the mixture was transferred to a sealed oven and reacted at 180°C for 12 hours. The reaction product was washed with ethanol to obtain S-doped MoSe2 two-dimensional nanomaterial (the atomic ratio of S:Se is 0.5:1), and the S-doped MoSe2 two-dimensional nanomaterial was dissolved in an ethanol solution to form a second ink.
[0107] Composite film embodiment 3
[0108] The difference between this embodiment and composite film embodiment 1 is that, in step (3), a second ink is configured to form a hole transport layer on the hole injection layer by the second ink, wherein the thickness of the hole transport layer is 30 nm.
[0109] Composite film embodiment 4
[0110] The difference between this embodiment and composite film embodiment 1 is that, in step (2), the first ink is configured by the following steps:
[0111] 140 mg of MoO2 nanowires were dispersed in 50 mL of deionized water, and after ultrasonic dispersion for 10 min, 8 mg of polydipropylenedimethylammonium chloride (PDDA) solution was added. After stirring for 30 min, the MoO2 precipitate was centrifuged and dissolved in deionized water. 16 mg of aluminum powder and 0.1 wt% of hydrolysis inhibitor (ammonium dihydrogen phosphate, NH4H2PO4) were added to form a MoO2 / Al mixed solution. The MoO2 / Al mixed solution was vacuum filtered, and then 100 mgAlCl3 was added to form a MoO2 / Al material containing 10 wt% Al by mass, which was used as a hole injection material. The hole injection material was dissolved in deionized water to form a hole injection ink with a concentration of 8 mg / mL.
[0112] Composite film embodiment 5
[0113] The difference between this embodiment and the composite film embodiment 1 is that, in step (2), the first ink is configured by the following steps:
[0114] 90 mg of MoO2 nanowires were dispersed in 50 mL of deionized water, and after ultrasonic dispersion for 10 min, 8 mg of polydipropylenedimethylammonium chloride (PDDA) solution was added. After stirring for 30 min, the MoO2 precipitate was centrifuged and dissolved in deionized water. 38 mg of aluminum powder and 0.1 wt% of hydrolysis inhibitor (ammonium dihydrogen phosphate, NH4H2PO4) were added to form a MoO2 / Al mixed solution. The MoO2 / Al mixed solution was vacuum filtered, and then 130 mg of AlCl3 was added to form a MoO2 / Al material containing 30 wt% Al by mass, which was used as a hole injection material. The hole injection material was dissolved in deionized water to form a hole injection ink with a concentration of 8 mg / mL.
[0115] Composite film embodiment 6
[0116] The difference between this embodiment and composite film embodiment 1 is that after step (3), the following steps are further included:
[0117] Step (4), preparing a third ink, and forming an interface modification layer on the hole transport layer by the third ink, wherein the thickness of the interface modification layer is 10 nm.
[0118] Wherein, the third ink is configured by the following steps:
[0119] 0.1mmol of molybdenum acetylacetonate and 0.1mmol of nickel nitrate were dissolved in 14ml of isopropanol, stirred until fully dissolved, and transferred to a sealed oven, reacted at 180°C for 12h, and the reaction product was washed with ethanol to obtain a NiMo precursor, which was placed in a muffle furnace and calcined at 600°C for 2h to form a NiMoO4 hollow sphere structure with a diameter of 10nm, and the NiMoO4 hollow sphere structure was dissolved in isopropanol solvent to form an interface modification ink with a concentration of 3mg / mL.
[0120] Composite film embodiment 7
[0121] The difference between this embodiment and composite film embodiment 6 is that, in step (4), the third ink is configured by the following steps:
[0122] 0.14 mmol acetyl manganese and 0.16 mmol nickel nitrate were dissolved in 14 ml isopropanol, stirred until fully dissolved, and transferred to a sealed oven, reacted at 180°C for 12 hours, and the reaction product was washed with ethanol to obtain a NiMn precursor, which was placed in a muffle furnace and calcined at 800°C for 2 hours to form a NiMnO4 hollow sphere structure with a diameter of 10 nm, and the NiMnO4 hollow sphere structure was dissolved in isopropanol solvent to form an interface modification ink with a concentration of 3 mg / mL.
[0123] Composite film comparative example 1
[0124] The difference between this embodiment and composite film embodiment 1 is that, in step (3), the second ink is TFB solution.
[0125] The composite thin films prepared in the composite thin film embodiments 1 to 7 and the composite thin film comparative example 1 were used as hole functional layers to prepare single hole devices (HOD devices), and the hole injection efficiency was tested respectively, and the test results were plotted into a JV curve, as shown in FIG. Figure 3 shown.
[0126] according to Figure 3As shown, when the control output voltage is 3V, the current density measured by the HOD device containing composite film embodiment 1 is about 520mA / cm2; the current density measured by the HOD device containing composite film embodiment 2 is about 600mA / cm2; the current density measured by the HOD device containing composite film embodiment 3 is about 880mA / cm2; the current density measured by the HOD device containing composite film embodiment 4 is about 1250mA / cm2; the current density measured by the HOD device containing composite film embodiment 5 is about 1340mA / cm2; the current density measured by the HOD device containing composite film embodiment 6 is about 2200mA / cm2; the current density measured by the HOD device containing composite film embodiment 7 is about 1450mA / cm2; the current density measured by the HOD device containing composite film comparison example 1 is about 450mA / cm2.
[0127] By comparing the JV curves of composite film embodiments 1 to 3 and composite film comparison example 1, it can be seen that under the same output voltage conditions, the current density of the HOD device comprising composite film embodiments 1 to 3 is greater than that of the HOD device comprising composite film comparison example 1. Therefore, it can be seen that the hole injection efficiency of the composite film can be improved by improving the thermal conductivity of the hole transport layer.
[0128] By comparing the JV curves of composite film embodiments 4 to 5 with composite film embodiments 1 to 3, it can be learned that under the same output voltage conditions, the current density of the HOD device comprising composite film embodiments 4 to 5 is greater than that of the HOD device comprising composite film embodiments 1 to 3. Therefore, it can be learned that the hole injection efficiency of the composite film can be further improved by heating the carriers in the hole injection layer and passing through the hole transport layer with a certain heat conduction capability.
[0129] By comparing the JV curves of composite film embodiments 6 to 7 with composite film comparison examples 4 to 5, it can be learned that, under the same output voltage conditions, the current density of the EOD device comprising composite film embodiments 6 to 7 is greater than that of the HOD device comprising composite film embodiments 4 to 5. Therefore, it can be learned that by further arranging an interface modification layer on the hole transport layer to reduce the difference between the hole transport material and the quantum dot size, the hole injection efficiency of the composite film can be further improved. In addition, the current density of the HOD device comprising composite film embodiment 6 is greater than the current density of the HOD device comprising composite film embodiment 7. Therefore, it can be learned that the interface modification layer using the same transition metal element as the hole transport layer can improve the internal chemical stability of the composite film, thereby improving the hole injection efficiency of the composite film.
[0130] Light emitting device embodiment 1
[0131] Step (1), providing an anode layer.
[0132] Step (2), preparing a hole functional layer on the anode layer using the preparation method of the composite film embodiment 1.
[0133] Step (3), spin coating CdSe / CdS red quantum dot ink on the hole transport layer to form a red quantum dot light-emitting layer, wherein the thickness of the red quantum dot light-emitting layer is 20 nm.
[0134] Step (4), evaporating ZnO nanocrystals on the quantum dot light-emitting layer to form an electron transport layer, wherein the thickness of the electron transport layer is 30 nm.
[0135] Step (5), vapor depositing Ag on the electron transport layer to form a cathode layer, wherein the thickness of the cathode layer is 30 nm.
[0136] Light emitting device embodiment 2
[0137] The difference between this embodiment and the light emitting device embodiment 1 is that, in the step (2), the hole functional layer is prepared on the anode layer by using the preparation method of the composite thin film embodiment 2.
[0138] Light emitting device embodiment 3
[0139] The difference between this embodiment and the light emitting device embodiment 1 is that, in the step (2), the hole functional layer is prepared on the anode layer by using the preparation method of the composite thin film embodiment 3.
[0140] Light emitting device embodiment 4
[0141] The difference between this embodiment and the light emitting device embodiment 1 is that, in the step (2), the hole functional layer is prepared on the anode layer by using the preparation method of the composite thin film embodiment 4.
[0142] Light emitting device embodiment 5
[0143] The difference between this embodiment and the light emitting device embodiment 1 is that, in the step (2), the hole functional layer is prepared on the anode layer by using the preparation method of the composite thin film embodiment 5.
[0144] Light emitting device embodiment 6
[0145] The difference between this embodiment and the light emitting device embodiment 1 is that, in the step (2), the hole functional layer is prepared on the anode layer by using the preparation method of the composite thin film embodiment 6.
[0146] Light emitting device embodiment 7
[0147] The difference between this embodiment and the light emitting device embodiment 1 is that, in the step (2), the hole functional layer is prepared on the anode layer by using the preparation method of the composite thin film embodiment 7.
[0148] Light-emitting device comparative example 1
[0149] The difference between this embodiment and the light emitting device embodiment 1 is that, in the step (2), a hole functional layer is prepared on the anode layer by using the preparation method of the composite thin film comparative example 1.
[0150] The performance tests were performed on the light-emitting devices prepared in light-emitting device embodiments 1 to 7 and light-emitting device comparative example 1. The test results are shown in Table 1.
[0151] Among them, the external quantum efficiency (EQE) of each photoelectric device is tested by an external quantum efficiency optical testing instrument; each photoelectric device is driven with a constant current of 2mA, and the time required for the photoelectric device to decay from an initial brightness of 1000nit to a brightness of 950Nit is measured by a life aging device; the voltage value of each photoelectric device at a brightness of 1nit is detected by an IV tester and recorded as the turn-on voltage, wherein the turn-on voltage is related to the recombination of hole-electron pairs, and the lower the turn-on voltage, the better the recombination of hole-electron pairs.
[0152]
[0153] Table 1
[0154] According to the records in Table 1, by comparing the test results of light-emitting device embodiments 1 to 3 with the light-emitting device comparative example 1, it can be learned that the transmission of hot carriers through the hole transport layer and the interface modification layer formed by the S-doped selenide two-dimensional nanomaterial can improve the external quantum efficiency of the optoelectronic device, extend the service life of the optoelectronic device and reduce the turn-on voltage.
[0155] By comparing the test results of light-emitting device embodiments 1 to 3 with light-emitting device embodiments 4 to 5, it can be learned that the material of the hole injection layer adopts a mixed material formed by transition metal oxide, aluminum powder and molten salt, so that the holes are heated to form hot carriers, and are transmitted through the hole transport layer with a certain heat conduction capability, which can further improve the external quantum efficiency of the optoelectronic device, extend the service life of the optoelectronic device and reduce the start-up voltage.
[0156] By comparing the test results of light-emitting device embodiments 4 to 5 with those of light-emitting device embodiments 6 to 7, it can be concluded that adding an interface modification layer between the hole transport layer and the quantum dot light-emitting layer can further improve the external quantum efficiency of the optoelectronic device, extend the service life of the optoelectronic device and reduce the start-up voltage.
[0157] To summarize, in the embodiments of the present application, a hole injection layer is used to heat holes to form hot carriers, and the hot carriers are received by a hole transport layer and an interface modification layer with good thermal conductivity and transmitted to the quantum dot light-emitting layer. This can improve the external quantum efficiency of the optoelectronic device, extend the service life of the optoelectronic device, increase the number of holes injected into the quantum dot light-emitting layer in the optoelectronic device, promote the charge balance of the quantum dot light-emitting layer, and thus improve the luminous efficiency and service life of the optoelectronic device.
[0158] Obviously, the embodiments described above are only some embodiments of the present application, rather than all embodiments. The preferred embodiments of the present application are given in the accompanying drawings, but they do not limit the patent scope of the present application. The present application can be implemented in many different forms. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive. Although the present application is described in detail with reference to the aforementioned embodiments, for those skilled in the art, it is still possible to modify the technical solutions recorded in the aforementioned specific implementation methods, or to perform equivalent replacement of some of the technical features therein. Any equivalent structure made using the contents of the specification and drawings of this application, directly or indirectly used in other related technical fields, is similarly within the scope of patent protection of this application.
Claims
1. A film, characterized in that: include: A first film, wherein the first film comprises a selenide two-dimensional nanomaterial containing a doping element, wherein the atomic radius of the doping element is smaller than the atomic radius of the selenium element.
2. The film according to claim 1, characterized in that The atomic ratio of the doping element to the selenium element is (0.5-1):
1.
3. The film according to claim 1, characterized in that The material of the selenide two-dimensional nanomaterial is selected from transition metal selenides, and the transition metal selenides are selected from at least one of molybdenum selenide, titanium selenide, vanadium selenide, rhenium selenide, cadmium selenide, zirconium selenide, hafnium selenide, tantalum selenide, tungsten selenide, and manganese selenide; and / or The doping element is selected from Group VIA elements; and / or The thickness of the first film is in the range of 20 to 50 nm.
4. A composite film, characterized in that: include: A first film, wherein the first film is the film according to any one of claims 1 to 3; A second film, wherein the first film is disposed on the second film, and the second film comprises a composite material, wherein the composite material comprises a mixed transition metal oxide, a molten salt and aluminum.
5. The composite film according to claim 4, characterized in that In the composite material, the mass percentage of the transition metal oxide is 40wt% to 60wt%; The mass percentage of the molten salt is 30wt% to 60wt%; The mass percentage of aluminum is 10wt% to 30wt%.
6. The composite film according to claim 4 or 5, characterized in that: The composite film further includes a third film. The first film is arranged between the second film and the third film. The third film is made of an interface modification material.
7. The composite film according to claim 6, characterized in that: The interface modification material is a hollow-shell structure, wherein the shell material of the hollow-shell structure is selected from transition metal compounds.
8. The composite film according to claim 7, characterized in that: The transition metal oxide is at least one selected from molybdenum trioxide, titanium dioxide, vanadium trioxide, rhenium heptoxide, chromium trioxide, zirconium dioxide, hafnium oxide, tantalum pentoxide, tungsten trioxide, and manganese dioxide; and / or The molten salt is selected from AlCl3 or Al2O3; and / or The transition metal compound is selected from at least one of molybdates, titanates, vanadates, rhenates, cadmates, zirconates, hafnates, tantalates, tungstates and manganates; and / or The thickness of the second film is in the range of 20 to 50 nm; and / or The diameter of the hollow-shell structure is in the range of 5 to 10 nm; and / or The thickness of the third film is in the range of 5 to 10 nm.
9. The composite film according to claim 8, characterized in that The first film, the second film and the third film have the same transition metal element.
10. A photoelectric device, characterized in that: include: A stacked anode layer, a hole functional layer, a quantum dot light emitting layer, an electronic functional layer and a cathode layer; Wherein, the hole functional layer adopts the composite film as described in any one of claims 4 to 9.
11. The optoelectronic device according to claim 10, characterized in that: The composite film comprises a first film, a second film and a third film which are stacked; The second film is disposed on the anode layer and serves as a hole injection layer; The first film is disposed on the second film to serve as a hole transport layer; The third film is arranged on the first film and serves as an interface modification layer.
12. The optoelectronic device according to claim 10, characterized in that: The material of the anode layer and / or cathode layer includes at least one of a metal, a carbon material and a metal oxide, wherein the metal includes at least one of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes at least one of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a doped or undoped metal oxide, including at least one of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, or includes a composite electrode in which a metal is sandwiched between doped or undoped transparent metal oxides, wherein the composite electrode includes at least one of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The electronic functional layer includes an electron transport layer, and the material of the electron transport layer includes an inorganic material and / or an organic material. The inorganic material is selected from at least one of doped or undoped zinc oxide, barium oxide, aluminum oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, nickel oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc tin, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, and barium titanate, and the doped element includes at least one of aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium; the organic material is selected from at least one of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene compounds, and hydroxyquinoline compounds; and / or The material of the quantum dot light-emitting layer includes at least one of single-structure quantum dots and core-shell structure quantum dots. The core material and shell material of the core-shell structure quantum dots are respectively selected from at least one of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. Among them, the II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZ At least one of CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI compounds include SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, S The group III-V compounds include at least one of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb; the group I-III-VI compounds include but are not limited to at least one of CuInS2, CuInSe2 and AgInS2.
13. A display device, characterized in that: The display device comprises the optoelectronic device according to any one of claims 10 to 12.